Entrustable professional activities for apheresis medicine education. Issue 10 (5th August 2020) - Pagano, Monica B.; Treml, Angela; Stephens, Laura D.; Joshi, Sarita; Li, Yanhua; Lopez‐Plaza, Ileana; Poyyapakkam, Srivaths; Schwartz, Joseph; Tanhehco, Yvette; Zantek, Nicole D.
Abstract: Background: Entrustable professional activities (EPAs) are well‐defined, executable, observable, and measurable activities that are performed by a trainee and can be performed independently as training progresses. The purpose of this study is to develop EPAs specific for the practice of apheresis medicine (AM). Methods: Members of the American Society for Apheresis Graduate Medical Education subcommittee developed a list of 28 apheresis medical activities linked to Accreditation Council for Graduate Medical Education milestones and competencies in five areas: (a) consultation, (b) clinical care for therapeutic apheresis, (c) clinical care for donor collections, (d) test optimization, and (e) vascular access. Ten AM experts using a validated tool to measure the quality of the EPAs (QUEPA) evaluated these activities with use of a Likert scale. Per group consensus, an activity was considered acceptable for each domain if it had received an average score greater than 3.7, and it was rated 4 or 5 (agree or strongly agree) by at least 70% of experts. Results: Of the 28 activities, 11 did not have acceptable QUEPA scores: 7 activities were rated as unobservable, 4 were rated unfocused, 2 were rated unrealistic and not generalizable, and 2 were rated as not addressing multiple competencies. Four activities had unacceptable scores in more than one domain. Subcommittee members edited these 11 activities over two review cycles to produce a final list of 26 activities. Conclusion: A set of practical, focused, and observable EPAs in AM were systematically developed. These EPAs can be used to assess and support trainee performance in AM.